The Latest COVID-19-associated Croup Rate in Children: A Retrospective Cohort Study from the TriNetX US Collaborative Networks - Ya-Chun Hu; Pei-Lun Liao; Ko-Huang Lue; Hai-Lun Sun (Pediatric Respirology and Critical Care Medicine)
Background: Croup (laryngotracheobronchitis) is the most common pediatric disease often associated with viral infection. The incidence of croup was also high during the coronavirus disease 2019 (COVID-19) pandemic.